PENANGANAN JALAN PADA TEROWONGAN GEURUTEE DENGAN MENGGUNAKAN LIFE CYCLE COST ANALYSIS - M. Akmal; Sugiarto Sugiarto; Noer Fadhly (Prodi Magister Teknik Sipil Unsyiah, 2021)
In Indonesia, especially in Aceh, the type of flexible pavement is more dominant than rigid pavement, better than rigid reinforcement of 24.15%. By further reducing the asphalt raw material that exists on the earth and many flexible pavement constructions increase faster than the age of the plan. For this reason, it is necessary to conduct a study to obtain an illustration of the cost of road repairs during the life of the plan, known as Life Cycle Cost Analysis (LCCA) for both types of pavement. The purpose of this study was to obtain a way of handling costs and a higher age level between flexible pavements with rigid pavement based on the LCCA method. This research will be carried out on the Lintas Barat Selatan National road KM 60 + 450 / K.027 with a simulation (prediction) of road handling and costs during the service life of the plan (40 years) which began since construction, construction, routine maintenance, continuous maintenance / periodic until firm (recycling) of the two types of pavement. The life cycle cost analysis using the Life Cycle Cost Analysis (LCCA) method shows a trend that occurs between the types of pavement where the flexible pavement value on each of the three discount factors shows a higher value compared to rigid pavement, with an average difference of choice that is equal to Rp. 16,359,761,474, - with a decrease in value of 25%. Life cycle cost analysis (LCCA) is Rigid Pavement.